IMPROVING THE WRITING SKILLS OF MIDDLE SCHOOL TESOL STUDENTS USING BLOG BASED LEARNING (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This study examines the effectiveness of blog-based learning in improving the writing skills of middle school students studying English as a foreign language (TESOL context). Writing is often considered one of the most challenging language skills for learners at this level due to limited vocabulary, low motivation, and anxiety related to written expression. The research aims to explore how the use of educational blogs can support the development of students’ writing accuracy, coherence, and overall engagement in the learning process.The study is based on a mixed-methods approach and was conducted with middle school learners during regular English lessons. Blog-based activities included short written posts, peer comments, and teacher feedback published in an online environment. The effectiveness of the method was evaluated through pre- and post-writing tests, as well as observation and analysis of students’ written work. The findings suggest that blog-based learning has a positive impact on students’ writing skills and motivation. Learners demonstrated improved confidence in expressing their ideas, greater interest in writing tasks, and increased interaction with peers. The use of blogs also encouraged a more learner-centered and interactive learning environment. The results of the study may be useful for English language teachers seeking practical digital tools to enhance writing instruction at the middle school level.